PENGARUH REWARD TERHADAP KINERJA KARYAWAN: PERAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SEBAGAI PEMEDIASI (Survei pada Karyawan Sales Force Otomotif di Wilayah Surakarta) - Rohwiyati, Praptiestrini & (Universitas Slamet Riyadi, 2018)
This research aims to analyses effect (1) reward on job satisfaction (2) reward on the organizational commitment (3) reward on performance (4) job satisfaction on performance (5) organizational commitment on performance (6) reward on performance mediated by job satisfaction (7) reward on performance mediated organizational commitment. This research using samples of 70 automotive sales force in Surakarta region. To test the hypothesis using path analysis. The result shows that (1) reward has significance effect on job satisfaction; (2) reward has not significance effect on organizational commitment, (3) reward has significance effect on performance; (4) job satisfaction has significance effect on performance; (5) organizational commitment has significance effect on performance; (6) effect reward on sales force performance mediated by job satisfaction; (7) effect reward on sales force performance mediated by organizational commitment.Keywords: reward, job satisfaction, organizational commitment, sales force performance